An efficient and sustainable biodiesel production in a mechanochemical pilot reactor under heterogeneous catalysis - Malpartida-García, Irene; Maireles-Torres, Pedro Jesús; Lair, Valentin; Halloumi, Samy; Thiel, Julien; Lacoste, François (My University, 2018)
Fatty acid methyl esters (FAME) produced from vegetable oils or animal fats by transesterification, or from the esterification of fatty acids, with methanol, is labeled as ‘‘Biodiesel”. Current industrial processes for biodiesel production are mainly based on homogeneous catalysis, in presence of an alkali hydroxide or methoxide dissolved in methanol, a large excess of methanol (methanol:oil molar ratio > 6), a temperature around 60 ºC and 1-2 h of reaction. However, this process suffers from different drawbacks, mainly related with the generation of large amount of wastewater associated to the washing and neutralization steps, the non-recovery of the homogeneous catalyst, or the formation of stable emulsions difficult to separate. These problems cause an increase of the overall biodiesel production cost. To overcome them, different approaches have been proposed, such as the use of heterogeneous catalysis, CO2 under supercritical conditions or enzymes, coupled to microwave and ultrasonic systems as alternative to conventional heating. In the present communication, a new mechanochemical reactor is used for the transesterification reaction that promotes the oil-methanol mixing, minimizing the mass transfer problems associated to the immiscibility of reactant mixtures. Moreover, in order to achieve a more sustainable biodiesel production process, a new heterogeneous basic catalyst is prepared from calcium oxide and glycerol, the by-product of biodiesel industry.
Keywords: Biodiesel; Heterogeneous catalysis; Mechanosynthesis; Calcium glyceroxide